Vjeran Pavlaković, Davor Pauković, ur., Framing the Nation and Collective Identities. Political Rituals and Cultural Memory of the Twentieth-Century Traumas in Croatia (London: Routledge, 2019), 245 str. (Časopis za suvremenu povijest, 2020)
Prikaz knjige